2015
DOI: 10.1007/s00021-015-0201-1
|View full text |Cite
|
Sign up to set email alerts
|

Singular Limits of Voigt Models in Fluid Dynamics

Abstract: ABSTRACT. We investigate the long-term behavior, as a certain regularization parameter vanishes, of the three-dimensional Navier-Stokes-Voigt model of a viscoelastic incompressible fluid. We prove the existence of global and exponential attractors of optimal regularity. We then derive explicit upper bounds for the dimension of these attractors in terms of the three-dimensional Grashof number and the regularization parameter. Finally, we also prove convergence of the (strong) global attractor of the 3D Navier-S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…For every fixed ε > 0 and β > 0, the semigroup S ε,β (t) possesses an exponential attractor E ε,β , and the same is true for the limiting semigroup S 0,0 (t) (see [9]). Again, the task is proving the convergence E ε,β → E 0,0 as ε → 0 and β → 0, in the sense of the symmetric Hausdorff distance.…”
Section: IImentioning
confidence: 83%
“…For every fixed ε > 0 and β > 0, the semigroup S ε,β (t) possesses an exponential attractor E ε,β , and the same is true for the limiting semigroup S 0,0 (t) (see [9]). Again, the task is proving the convergence E ε,β → E 0,0 as ε → 0 and β → 0, in the sense of the symmetric Hausdorff distance.…”
Section: IImentioning
confidence: 83%
“…21) and u(t) is a weak solution of 3D incompressible Navier-Stokes equation, i.e., u(t) ∈ O 0 .From the above argument, we have proved the following proposition.…”
mentioning
confidence: 77%
“…There are also a lot of literature on Navier-Stokes-α model [1,2,9,10,18]. Zelati and Gal [21] proved the existence of global and exponential attractors, then they prove the convergence of the (strong) global attractor of the 3D Navier-Stokes-Voight model to the (weak) global attractor of the 3D Navier-Stokes equation, i.e., they prove the convergence of the (strong) global attractor of the 3D Navier-Stokes-Voight model to the trajectory attractor of the 3D Navier-Stokes equation. But, they did not prove upper semicontinuity of trajectory attractors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they showed that as the viscosity coefficient goes to zero, the weak solutions of the Navier-Stokes-Voight equations converge to the weak solutions of the inviscid simplified Bardina model in appropriate norm. The authors in [40] investigated the long-term behavior of the three-dimensional Navier-Stokes-Voigt model as the regularization parameter vanishes and extended the results of [25]. They established the existence of global and exponential attractors of optimal regularity.…”
mentioning
confidence: 98%